2021
DOI: 10.1039/d1sc02154k
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanoribbon-based supramolecular ensembles with dual-receptor targeting function for targeted photothermal tumor therapy

Abstract: Triple negative breast cancer (TNBC) is one of the most malignant subtypes of breast cancer. Here, we report the construction of graphene nanoribbon (GNR)-based supramolecular ensembles with dual-receptor (mannose and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…TEM was used for the visualization of the morphological changes of Pseudomonas aeruginosa (ATCC 27853, 10 6 CFU ml −1 ) in the presence of the AgNP/ChS/GNR nanocomposite; while, AgNP, ChS, AgNP/ChS and GNR were used as controls ( Figure 2 ). Considering the outstanding photothermal property of GNR ( Huang et al, 2018 ; Mousavi et al, 2019 ; Johnson et al, 2020 ; Yu et al, 2020 ; Dou et al, 2021 ), near-infrared (NIR) irradiation (808 nm, 1 W cm −2 ) was used to evaluate the PTT effect of the materials ( Figure 2A ). Initially, we observed rod-like morphology in the TEM images of P. aeruginosa .…”
Section: Resultsmentioning
confidence: 99%
“…TEM was used for the visualization of the morphological changes of Pseudomonas aeruginosa (ATCC 27853, 10 6 CFU ml −1 ) in the presence of the AgNP/ChS/GNR nanocomposite; while, AgNP, ChS, AgNP/ChS and GNR were used as controls ( Figure 2 ). Considering the outstanding photothermal property of GNR ( Huang et al, 2018 ; Mousavi et al, 2019 ; Johnson et al, 2020 ; Yu et al, 2020 ; Dou et al, 2021 ), near-infrared (NIR) irradiation (808 nm, 1 W cm −2 ) was used to evaluate the PTT effect of the materials ( Figure 2A ). Initially, we observed rod-like morphology in the TEM images of P. aeruginosa .…”
Section: Resultsmentioning
confidence: 99%
“…Initially, mannosylated conjugated MUC1 generated both antitumor B and T cell responses in preclinical and clinical studies [241,242]. More recently, MMR-targeting was proposed for TAM modulation with siRNA [243] or DNA-based vaccines [244] to favour photothermal tumour therapy [245], or as carriers of chemotherapeutic drugs [246]. In particular, a recent study showed that mannose-functionalized nanoscaffolds as carriers of chemotherapeutic agents [247] efficiently killed tumours, although more in vivo studies are needed to confirm their efficiency.…”
Section: Taca and Clr Targeting For Cancer Immunotherapymentioning
confidence: 99%
“…Extensive efforts from the group of He have led to the development of receptor-targeting fluorescence imaging and theranostic systems using graphene oxide (GO) based supramolecular glycocomposites. (Ji et al, 2015;Dou et al, 2021). Many disease-related processes involve glycoligand-receptor interactions.…”
Section: Current State Of the Artmentioning
confidence: 99%